Changes in phenolic compounds, antioxidant potential and antinutritional factors of Teff (Eragrostis tef) during different thermal processing methods. (5th July 2021) - Kataria, Ankita; Sharma, Savita; Dar, B.N.
Summary: Brown teff exhibits superior antioxidant characteristics and is categorised as a super grain. Thermal treatments are common processing steps prior to domestic consumption or at industrial production. This study aimed to analyse the effect of thermal processing treatments (moist heat – conventional heating (2, 3.5 and 5 min), autoclaving (121°C for 15 min); dry heat – roasting (5, 7.5 and 10 min), microwave processing (2, 3.5 and 5 min)) at different experimental conditions on total phenolic content (TPC), total flavonoid content (TFC), potential antioxidant activities, antioxidant potency composite index and antinutritional factors of brown teff ( Eragrostis tef ). Raw grains contained appreciable quantities of TPC (2.52 mg gallic acid equivalents/g) and TFC (14.68 mg quercetin equivalents/g), but roasting and microwave processing further improved their levels (10–24%). Results showed that microwave processed grains exhibited higher antioxidant activities with the highest average antioxidant potency composite index (81.52). Phytic acid and tannins were effectively reduced by all the thermal processes (26–37%). During, roasting and microwave processing, the reduction in saponins occurred after higher processing times. These results suggest that thermal processing can be utilised to improve the antioxidant properties along with a reduction of antinutritional compounds to approve regular consumption of this super grain. Abstract : Teff is a rich source of bioactive molecules. Thermal processing except autoclaving enhanced the bioactive constituents of Teff. Roasting and microwave processing highly improved the antioxidant activities of Teff. Thermal processing reduced levels of phytates and tannins in Teff.